Surface and vertical dimensional changes of mineral trioxide aggregate and biodentine in different environmental conditions - Aksel, Hacer; Küçükkaya Eren, Selen; Askerbeyli Õrs, Sevinc; Karaismailoğlu, Eda (FapUNIFESP (SciELO), 2018)
Surface changes in biological environments are critical for the evaluation of physical and biological activity of biomaterials. Objective: This study investigated surface alterations of calcium silicate-based cements after exposure to different environments.Material and Methods: Forty-eight cylindrical cavities were prepared on root surfaces. The cavities were filled using ProRoot MTA or Biodentine and assigned to four subgroups (n=6): dry, wet, acidic, and blood. Surface topographies were evaluated using an optical profilometer for 28 days, and the roughness of the material surfaces was quantified. Vertical dimensional change was measured by determining the height difference between the material surface and the flat tooth surface. Data were compared with a two-way repeated measures ANOVA and Bonferroni tests.Results: In dry condition, the surface roughness of MTA or Biodentine was constant up to 3 days (p>0.05) but decreased after 28 days (p<0.05). In dry condition, ProRoot MTA presented constant surface level through time, while Biodentine showed decreased surface level after 28 days. In wet condition, the roughness and the surface levels of both materials increased after 1 day (p<0.05). Neither the surface roughness nor the levels of the materials showed significant changes in acidic conditions (p>0.05). Both materials showed the highest roughness in blood conditions on the 1st day (p<0.05), while the surface roughness in blood decreased dramatically after 28 days. The roughness of Biodentine was higher in wet conditions up to 3 days compared with ProRoot MTA (p<0.05). Likewise, in blood condition, Biodentine showed higher roughness on the 28th day than ProRoot MTA (p<0.05).Conclusions: Dry, wet, and blood conditions had a time-dependent effect on the surface roughness and vertical dimensional changes of the materials. However, acidic conditions did not affect the roughness and the surface level of the materials.
Keywords: Time Factors; Surface Properties; Root Canal Filling Materials; Calcium silicate-based cement; Reference Values; Materials Testing; Humans; Aluminum Compounds; Analysis of Variance; Silicates; Reproducibility of Results; Water; RK1-715; Oxides; Calcium Compounds; Roughness; Biodentine; Drug Combinations; Blood; MTA; Dentistry; Original Article; Profilometer; 4. Education